2009
DOI: 10.1051/ebr/2010002
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional prediction of maize pollen dispersal and cross-pollination, and the effects of windbreaks

Abstract: With the extensive adoption of transgenic crops, an understanding of transgene flow is essential to manage gene flow to non-GM crops. Thus, a flexible and accurate numerical model is required to assess gene flow through pollen dispersal. A three-dimensional atmospheric model combined with a diffusion transport model would be a useful tool for predicting pollen dispersal since it would be flexible enough to incorporate the effects of factors such as the spatial arrangement of crop combinations, land use, topogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…pdhm2 uses a plume model, which is a kind of quasi-mechanistic model that has been widely used for the prediction of diffusion of atmospheric pollutants. The model has the advantage of rapid calculation time, in contrast to the Lagrangian model (Ushiyama et al, 2009), which traces the movement of each particle one by one. pdhm2 has flexibility with respect to grid size and calculation time from the beginning to the end of the flowering that is set by the header file pdhm.…”
Section: Main Programmentioning
confidence: 99%
See 2 more Smart Citations
“…pdhm2 uses a plume model, which is a kind of quasi-mechanistic model that has been widely used for the prediction of diffusion of atmospheric pollutants. The model has the advantage of rapid calculation time, in contrast to the Lagrangian model (Ushiyama et al, 2009), which traces the movement of each particle one by one. pdhm2 has flexibility with respect to grid size and calculation time from the beginning to the end of the flowering that is set by the header file pdhm.…”
Section: Main Programmentioning
confidence: 99%
“…Pollen flow from GM maize has also been well studied (Jarosz et al, 2003;Jarosz et al, 2005;Kawashima et al, 2004;Sanvido et al, 2008;Ushiyama et al, 2009), because Bt (Bacillus thuringiensis) maize has high productivity due to the reduction of insect damage and because cross-pollination can occur over long distances (hundreds of meters or more). Some of the above studies in Europe were conducted in projects that aim to promote the introduction of GM crops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. ( 1993( Maki et al, 2004 ( Wang and Takle, 19951996Wang et al, 2001Bourdin and Wilson, 2008) (Cleugh, 1998Takahashi et al, 1998 (Ushiyama et al, 2009b) ( ) : Ushiyama et al, (2009b) 10 50 m 1 1 2 3 4 5…”
Section: ( )mentioning
confidence: 99%
“…found that a vegetative border of a tall annual grass (sorghum-sudangrass hybrids) reduced pollen transport from a maize field. Ushiyama et al [2010] evaluated fences as windbreaks in maize fields, but found little effect on pollen dispersal. Although research has shown that pollen concentration decreases with distance from the source [Ecker et al, 2013, Chamecki and Meneveau, 2011, Okubo and Levin, 1989, there are no studies on the effect of typical farm windbreaks (one or more rows of cultivated trees or shrubs) or narrow forest stands on pollen dispersal.…”
Section: Introductionmentioning
confidence: 99%